2019
DOI: 10.1111/bjh.15824
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomized, multicentre, double blind, active controlled trial to compare the efficacy and safety of two different anagrelide formulations in patients with essential thrombocythaemia – the TEAMET 2·0 trial

Abstract: Summary Anagrelide is an established treatment option for essential thrombocythaemia ( ET ). A prolonged release formulation was developed with the aim of reducing dosing frequency and improving tolerability, without diminishing efficacy. This multicentre, randomized, double blind, active‐controlled, non‐inferiority trial investigated the efficacy, safety and tolerability of anagrelide prolonged release (A‐ PR ) over a reference product in high‐risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Finally, in the randomized, double-blind active controlled, TEAM-ET trial, a anagrelide prolonged-release formulation was compared to reference product in 106 patients; the study showed non-inferiority of new formulation over the reference in reducing platelet count. Unfortunately, vascular events were not an endpoint of the study [98]. Combination of hydroxyurea and anagrelide in patients whose platelet counts was poorly controlled with monotherapy were shown safe and effective in an observational study in 347 patients [99].…”
Section: Treatment Of Patients With Etmentioning
confidence: 99%
“…Finally, in the randomized, double-blind active controlled, TEAM-ET trial, a anagrelide prolonged-release formulation was compared to reference product in 106 patients; the study showed non-inferiority of new formulation over the reference in reducing platelet count. Unfortunately, vascular events were not an endpoint of the study [98]. Combination of hydroxyurea and anagrelide in patients whose platelet counts was poorly controlled with monotherapy were shown safe and effective in an observational study in 347 patients [99].…”
Section: Treatment Of Patients With Etmentioning
confidence: 99%
“…Recently, an extended release formulation of anagrelide was developed that could offer a more convenient dosing schedule. 53 Ruxolitinib has been tested in ET intolerant or resistant to HU, but so far has not proven beneficial. 54,55 The ongoing RUXO-BEAT trial evaluates the role of ruxolitinib as first-line therapy in high-risk PV and ET, and results are awaited.…”
Section: Essential Thrombocythemiamentioning
confidence: 99%